A 1.6 Mb region on SSC2 is associated with antibody response to classical swine fever vaccination in a mixed pig population. Issue 6 (18th November 2022) - Mehrotra, Arnav; Bhushan, Bharat; Kumar, Amit; Panigrahi, Manjit; A., Karthikeyan; Singh, Akansha; Tiwari, Ashok K.; Pausch, Hubert; Dutt, Triveni; Mishra, Bishnu P.
Abstract: Classical Swine Fever (CSF) is a contagious viral disease of pigs which is endemic in several parts of the world, including India. Prophylactic vaccination using live attenuated vaccine is the preferred method of control. However, there is significant inter-individual variation in the antibody response to vaccination. In this study, we measured the E2 antibody blocking percentage after 21 days of CSF vaccination in a mixed pig population consisting of Landrace, indigenous Ghurrah pigs, and their crossbreds. A Genome Wide Association Study (GWAS) carried out using single-SNP and haplotype based methods detected a 1.6 Mb region on SSC2 (28.92−30.52 Mb) as significantly associated with antibody response to CSF vaccination. The significant region and 1 Mb flanking sequences encompass 3 genes – EIF3M, DNAJC24 and ARL14EP, which code for proteins involved in Pestivirus replication and host immune response system. Our results combined with previous studies on immune response of pigs present this region as a suitable candidate for future functional investigations.